Modelo quantitativo para avaliação de desempenho empresarial baseado em análise envoltória de dados com múltiplos fatores - Tavares, Necésio José Faria (2008)
DEA, Data Envelopment Analysis, is a non parametric modeling technique which came about in 1976 when three prominent researchers, Charnes, Cooper and Rhodes were in search of a procedure to evaluate productivity/efficiency without recourse to price information. Soon after, new and more complex models were developed with wide acceptance among researchers mainly in the Management Sciences field. Nowadays, DEA finds its use in areas like hospitals, banks, industries, universities and capital markets. This research aims at using DEA as a tool to evaluate the top Brazilian companies listed in the local stock exchange based in a model which simultaneously combine several inputs to generate income and net profits. A second step evaluates how shareholders value the income and profit generated by the firms. A third step evaluates how efficiently each firm succeeds in directly transforming its endowments in shareholder´s value. The proposed model goes further in that it uses outputs produced by a first stage evaluation, like income and net profit, as inputs to the second phase evaluation. Furthermore, this research combines DEA with the Malmquist Productivity Index providing information on how the largest companies went along in between 2001-2006, as far as productivity and efficiency is concerned.